Effect of the supplementation with organic acids and essential oils on sow productivity - Alvarado-Núñez, Jorge Arturo (2021)
Essential Oils plus Organic Acids (EO+OA) compounds are proposed as an alternative to growth promoting antibiotics. The objective of this work was to evaluate the effects of supplementing a commercial formulation of EO+OA on productivity of lactating sows and their piglets in the Costa Rican dry tropics. Forty-two sows grouped in three evaluation periods and seven parity groups, were assigned to two treatments: Control and Treated (2 kg/ton EO+OA supplement). The variables evaluated in the sows were pre-farrrowing and post-weaning weight, backfat thickness (prior farrowing and post weaning), open days, feed intake, gestation length and pregnancy rate. The weaning weight, total born number, born alive, stillbirths, mummified piglets, and weaning mortality were compared on the litter. There were no significant differences between the treatments for any of the variables (p>0.05), however, trends (p<0.1) on total born (Control: 11.6; Treated: 13.7) and mummified piglets (Control: 0.3; Treated: 0.8) were found. The supplement composition and the lack of pathogenic challenge might be the causes behind the observed lack of effects. In conclusion, the supplementation with EO+OA had no effects on sow productivity.